College Students’ Engagement in Violence Prevention Discussions with Peers - Hoxmeier, Jill C. (Journal of interpersonal violence, 2023)
The bystander intervention (BI) model recognizes a range of prosocial helping behaviors individuals can perform to support sexual and dating violence (S/DV) prevention efforts. Individuals can demonstrate a commitment to ending violence through proactive BI, such as participating in prevention initiatives or talking with peers about ways to keep safe, which are different than reactive BI behaviors when violence is underway. Given the anchoring of the BI model in Diffusion of Innovation Theory, which articulates the uptake of new behaviors throughout a population or community and the role of change agent aids in that process, investigating demographic, and other individual-level correlates, of proactive behaviors may help identify those students who are particularly positioned to help diffuse and normalize anti-violence behaviors. The purpose of this study was to examine (1) the occurrence of students’ engagement in peer discussions about violence prevention in the past year and (2) the correlates of reporting to have those discussions among university students in a cross-sectional study implemented on two campuses in the Mid-Atlantic U.S. Results showed that the most common discussion was talking to friends about being safe in dating relationships and the least common was talking with friends about participating in violence-prevention-related activities, with 66.2% and 22.5% having done so, respectively. Women, younger students, and those reporting to know a survivor of either DV or SV were more likely to report having discussions, compared to men, older students, and those not knowing a survivor. Additional relationships were detected between other individual characteristics, knowledge about violence/victimization, and climate-related variables but differed depending on whether participants participated in the DV or SV-related survey module. Findings suggest the need for BI training initiatives to emphasize proactive engagement and peer discussions, and that gender continues to be a robust indicator of violence-prevention actions.